La fenomenología en el objeto arquitectónico: interpretación del modelo “Edificio Plaza”, en Chiquinquirá, Boyacá. (2022)
Phenomenology in design seeks to establish sensitive relationships between subject and object where through a game of strategies, induces the viewer to live a experience; however, design alone does not complete the task of moving the spectator, this in turn, must have a sensitive position before the work. In the phenomenological experiences, the role of the public square as a meeting place and development of the commercial activity, acquires vital sense in its quality of space of tradition in human contact; in it is found the coincidence of the encounter that offers collective cohesion for citizens. These social relations have been seen affected throughout history, and in the current context due to the appearance of covid, which turns the square into a place of contagion, which leads to the need to rethinking said space through a formal and functional exploration. The work of degree proposes the study of phenomenology applied to the architectural object, for the interpretation of the plaza building model, in Chiquinquirá, Boyacá, seeking to reestablish the user that social meeting space in a safe and habitable environment, transmitting popular memory and dignifying the architectural fact.